Biomass sensor technology transformation to optimize land potential and empower farmers in Sudimoro Village, Jombang - Zulfikar, Zulfikar; Nasirudin, Mohamad; Hariono, Tholib (Universitas Muhammadiyah Magelang, 2025)
This community service activity aims to empower farmers through the application of biomass-based land potential sensor technology transformation in Sudimoro Village, Megaluh District, Jombang Regency. The main challenges faced by the farmers include limited knowledge regarding land potential, persistent doubts about adopting technological innovations, and low practical skills in technology-based management. The urgency of this program lies in the need to enhance the capacity of farmers to optimally manage agricultural land sustainably with the support of modern technology. The implementation method included outreach, training, field demonstrations, and intensive mentoring for ten farmer participants. Evaluation results demonstrated significant improvements: knowledge increased from 42.5% to 82%, attitudes from 55% to 86.5%, and skills from 20% to 77%. Paired sample t-test analysis confirmed that these differences were statistically significant (p < 0.001) across all three aspects. These findings prove that the sensor technology-based intervention is capable of holistically increasing farmer capacity. Thus, the program has delivered a tangible impact on the empowerment of the farming community while serving as a model for sustainable agricultural innovation that can be replicated in other rural areas.